2012
DOI: 10.1111/j.1365-3059.2012.02598.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and diagnostics of stubby root and virus vector nematodes of the family Trichodoridae (Nematoda: Triplonchida) using ribosomal RNA genes

Abstract: Plant parasitic nematodes of the family Trichodoridae cause substantial yield losses in many agricultural crops. Rapid and accurate identification of trichodorids to the species level is critical for selection of appropriate measures for control. This study analysed 99 sequences of the D2-D3 expansion segments of the 28S rRNA gene and 131 sequences of the 18S rRNA gene from the stubby nematodes belonging to the genera Nanidorus, Paratrichodorus and Trichodorus. Species delimiting was based on the integration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…A single fragment of approximately 452 bp was amplifi ed for all studied individuals (Fig. 3) Kumari et al, 2007). Similarly, the ITS1 showed 1237/1255 identity to T. similis from the UK (AJ439523, Boutsika et al, 2004a) and 1359/1364 identity to T. similis from the Czech Republic (JN123317, Kumari and Subbotin, 2012).…”
Section: Molecular Studymentioning
confidence: 99%
See 1 more Smart Citation
“…A single fragment of approximately 452 bp was amplifi ed for all studied individuals (Fig. 3) Kumari et al, 2007). Similarly, the ITS1 showed 1237/1255 identity to T. similis from the UK (AJ439523, Boutsika et al, 2004a) and 1359/1364 identity to T. similis from the Czech Republic (JN123317, Kumari and Subbotin, 2012).…”
Section: Molecular Studymentioning
confidence: 99%
“…Previous records of trichodorids from the Czech Republic are from apple, birch, elm, grass, maple, oak, peach, pine, strawberry and sweet cherry (Kumari et al, 2007;Kumari & Decraemer, 2009, 2011Kumari, 2010;Kumari & Subbotin 2012). Research has been initiated in the Czech Republic to determine the presence or extent of trichodorids associated with potato.…”
Section: Introductionmentioning
confidence: 99%
“…Sequences of the new species from type locality (Chiba) were 125-126 bp longer than from Kagoshima, mainly due to insertion of 122 bp between the 807th and 808th site of the latter rather than the result of changes in the number of repeats in microsatellites (De Luca et al, 2011). At the species level, such intra-individual variability of ITS sequences had been observed in Pratylenchus vulntts (up to 7%) and F. primitivus (up to 37%) (De Luca et al, 2011;Kumari & Subbotin, 2012). The sequence analysis revealed high variability not only between populations or isolates but also within the same individual.…”
Section: Ts2 Rdnamentioning
confidence: 90%
“…Bayesian analysis was performed to confirm the tree topology for each gene separately using MrBayes 3.1.0 (Huelsenbeck & Ronquist, 2001) running the chain for 10 6 generations and setting the 'burn in' at 1000. We used MCMC (Markov Chain Monte Carlo) methods within Nunn (1992) a Bayesian framework to estimate the posterior probabilities of the phylogenetic trees (Larget & Simon, 1999) using the 50 % majority-rule.…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Accurate identification of trichodorids to the species level is crucial to implement appropriate control measures for these nematodes. Typically, trichodorid identification is based on analysis of morphological and morphometrical HELMINTHOLOGIA, 51, 4: 323 -330, 2014 Morphological and molecular characterization of two isolates of Paratrichodorus porosus from Shenzhen, China (Boutsika et al, 2004;Riga et al, 2007;Duarte et al, 2011;Kumari & Subbotin, 2012). Kumari & Subbotin (2012) reported that analysis of the D2/D3 of the 28S rDNA sequence data set revealed four unidentified species of Trichodorus, and the partial 18S rDNA sequence data set distinguished four unidentified species of Trichodorus and two unidentified species of Paratrichodorus.…”
Section: Introductionmentioning
confidence: 99%